PENGARUH ETIKA JABATAN TERHADAP KINERJA APARATUR SIPIL NEGARA DISEKERTARIAT KOTA MANADO - SISO, ENGLIN; Ruru, Joorie Marhaen; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: The purpose of this study was to determine the effect on the performance of the ethics office at theState Secretariat of Civil Administrative Region city of Manado.The method used is the method of quantitative research korelasional.Responden are 36 people ASN / PNS taken byrandom sampling technique of structural official and executive employees / staff at the Regional SecretariatManado.Data used is primary data collected using questionnaires and assisted with interview techniques. Theanalysis technique used is a simple linear regression analysis and simple correlation / product moment.The result showed: (1) variable regression coefficient ethics office to the level of performance of the apparatus isvery significant posifive and (2) the correlation coefficient and the coefficient of determination variables ethicsoffice to the performance of the apparatus is high / strong and highly significant.Based on the results of these studies conclude is ethics office have functional relations / positive and significantimpact on the performance of the State Civil Apparatus (PNS) in the Regional Secretariat of Manado.According to the conclusion that the ethics office let be used as a tool or a means to improve the performance of theState Civil Apparatus.Keywords: ethics office, the performance of the apparatus.